A Kebijakan Bisnis Yang Berorientasi Pada Green Tourism Sebagai Implementasi Pasal 67 Undang-Undang Nomor 32 Tahun 2009 : green tourism, kebijakan bisnis, lingkungan hidup - Widiadnyani, I; Muhammad Panji Mahardika; Lily Marheni; I Nyoman Sukayasa (VYAVAHARA DUTA, 2025)
In an effort to preserve environmental sustainability and support sustainable development, green tourism policy has emerged as a strategic alternative. This article discusses the implementation of green tourism policy as a response to Article 67 of Law Number 32 of 2009 concerning Environmental Protection and Management. This research employs a qualitative approach with case study analysis in several tourist destinations that implement sustainable tourism principles. The findings indicate that the application of green tourism not only contributes to environmental preservation but also enhances the quality of tourist experiences and empowers local communiaties. Furthermore, this policy encourages collaboration among the government, tourism industry stakeholders, and communities to create a more environmentally friendly tourism ecosystem. The conclusion of this study underlines the importance of strengthening regulations and business policy support to expand the implementation of green tourism in Indonesia, as a concrete step towards achieving sustainable development goals